Analisis Perluasan Penutup Lahan Pada Kecamatan Sunggal Menggunakan Metode Geometri - Eka Rahayu (Query: Journal of Information Systems, 2020)
Land is a very important, because of natural resources for the continuity of human life in every activity.This study aims to produce a predominant recommendation future residential land needs, so it is useful for structuring the city of the residential area which is carried out on the territory Sunggal sub-district. It's useful as a tool in developing local area to give permission to build buildings. The data used is population census data from 2010 until 2014 based on the population of villages. In this research using geometrical methods for population growth analysis, so that the population density and residential land area required for 2015 are known, 2020, 2025 and 2030.Keywords: Land, Geometry, Population Census, Settlement